1995
DOI: 10.1111/j.1360-0443.1995.tb01039.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the determinants of safe injecting and condom use among injecting drug users

Abstract: A sample of 582 injecting drug users were interviewed as part of an evaluation of an AIDS prevention programme for drug users. This paper examines the biographic and predispositional determinants of five HIV preventive behaviours-equipment sharing (not receiving and not giving) and condom use (with regular partners, casual partners and sex clients). A two-stage sequential approach was adopted for a logistic regression analysis. Initially, to model each of the five preventive behaviours, biographical and drug u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Psychosocial variables related to risk include loss of close friends and family to AIDS, and depression, factors that were not measured in our study (Schilling et al, 1993). Others have reported that younger age was associated with safer sex practices (Myers et al, 1995), a finding again not reproduced here.…”
Section: Discussionmentioning
confidence: 53%
“…Psychosocial variables related to risk include loss of close friends and family to AIDS, and depression, factors that were not measured in our study (Schilling et al, 1993). Others have reported that younger age was associated with safer sex practices (Myers et al, 1995), a finding again not reproduced here.…”
Section: Discussionmentioning
confidence: 53%
“…Even so, less than half of HTV-f drug injectors, 46%, consistently used condoms. Friedman et al's findings are representative of other research (6,(17)(18)(19)(20). A study conducted by Kwiatkowski and Booth (21) compared the likelihood of engaging in unprotected sex between HTV+ crack smokers and HIV+ drug injectors.…”
Section: Introductionsupporting
confidence: 51%
“…[14][15][16][17] Some studies have found an association between syringe sharing and inconsistent condom use. 18,19 In the United States, sexual practices have a greater effect on HIV risk for women IDUs than for men. In Baltimore, high risk sexual activity surpassed risky drug use practices as the main predictor of HIV infection among women IDUs during the period observed; HIV incidence more than doubled among women IDUs who had an IDU sex partner.…”
Section: Women Who Inject Drugs Are Especially Vulnerablementioning
confidence: 99%